Failure Analysis and Reliability Study of NAND Flash-Based Solid State Drives - R. Sayyad; Sangram Redkar (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The research focuses on conducting failure analysis and reliability study to understand and analyze the root cause of Quality, Endurance component Reliability Demonstration Test (RDT) failures and determine SSD performance capability. It addresses essential challenges in developing techniques that utilize solid-state memory technologies (with emphasis on NAND flash memory) from device, circuit, architecture, and system perspectives. These challenges include not only the performance degradation arising from the physical nature of NAND flash memory, e.g., the inability to modify data in-place read/write performance asymmetry, and slow and constrained erase functionality, but also the reliability drawbacks that limits Solid State Drives (SSDs) performance.  In order to understand the nature of failures, a Fault Tree Analysis (FTA) was performed that identified the potential causes of component failures. In the course of this research, significant data gathering and analysis effort was carried out that led to a systematic evaluation of the components under consideration.